The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1109/tste.2020.3004630
|View full text |Cite
|
Sign up to set email alerts
|

Communication-Less Frequency Support From Offshore Wind Farms Connected to HVdc via Diode Rectifiers

Abstract: Before diode rectifier (DR) technology for connecting offshore wind farms (OWFs) to HVdc is deployed, indepth studies are needed to assess the actual capabilities of DRconnected OWFs to contribute to the secure operation of the networks linked to them. This study assesses the capability of such an OWF to provide communication-less frequency support (CLFS) to an onshore ac network. It is shown that the HVdc link's offshore terminal direct voltage can be estimated from measurements at the OWF's point of connecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…where R g3 and D 3 are respectively the frequency droop of the governor and damping factor of ac system B. The relation between power and frequency of onshore A considering (14) cab be express as…”
Section: B Frequency Support With Droop Controlmentioning
confidence: 99%
“…where R g3 and D 3 are respectively the frequency droop of the governor and damping factor of ac system B. The relation between power and frequency of onshore A considering (14) cab be express as…”
Section: B Frequency Support With Droop Controlmentioning
confidence: 99%
“…As a result, traditional droop control is incapable of coordinating dc voltage regulation, frequency support, and power dispatch. When it comes to frequency support, numerous studies have found that control schemes that provide frequency support have a very positive impact [13][14][15][16]. Paper [17] uses pilot voltage droop (PVD) control to enhance the dc voltage regulation and frequency deviation sharing.…”
Section: Introductionmentioning
confidence: 99%
“…The literature proposes various ways to support the frequency of AC systems such as wind power-HVDC systems [16]- [18], multi-terminal HVDC grids [19]- [21], and fast frequency reserve sources [22], [23]. Furthermore, assuming advanced communication infrastructure and adaptive control capabilities, interesting control methods were assessed in [24]- [27].…”
Section: Introductionmentioning
confidence: 99%